The High Energy X-ray Probe (HEX-P): probing accretion onto stellar mass black holes - Connors, Riley M.T.; Tomsick, John A.; Draghis, Paul; Coughenour, Benjamin; Shaw, Aarran W.; García, Javier A.; Walton, Dominic; Madsen, Kristin; Stern, Daniel; Rodriguez, Nicole Cavero; Dauser, Thomas; Del Santo, Melania; et al. (Frontiers in Astronomy and Space Sciences, 2023)
Accretion is a universal astrophysical process that plays a key role in cosmic history, from the epoch of reionization to galaxy and stellar formation and evolution. Accreting stellar-mass black holes in X-ray binaries are one of the best laboratories to study the accretion process and probe strong gravity—and most importantly, to measure the angular momentum, or spin, of black holes, and its role as a powering mechanism for relativistic astrophysical phenomena. Comprehensive characterization of the disk-corona system of accreting black holes, and their co-evolution, is fundamental to measurements of black hole spin. Here, we use simulated data to demonstrate how key unanswered questions in the study of accreting stellar-mass black holes will be addressed by the High Energy X-ray Probe (HEX-P). HEX-P is a probe-class mission concept that will combine high spatial resolution X-ray imaging and broad spectral coverage (0.2–80 keV) with a sensitivity superior to current facilities (including XMM-Newton and NuSTAR) to enable revolutionary new insights into a variety of important astrophysical problems. We illustrate the capability of HEX-P to: 1) measure the evolving structures of black hole binary accretion flows down to low (≲ 0.1%) Eddington-scaled luminosities via detailed X-ray reflection spectroscopy; 2) provide unprecedented spectral observations of the coronal plasma, probing its elusive geometry and energetics; 3) perform detailed broadband studies of stellar mass black holes in nearby galaxies, thus expanding the repertoire of sources we can use to study accretion physics and determine the fundamental nature of black holes; and 4) act as a complementary observatory to a range of future ground and space-based astronomical observatories, thus providing key spectral measurements of the multi-component emission from the inner accretion flows of black hole X-ray binaries.
CRIS-Team Scopus Importer:2024-12-16
Keywords: accretion; binaries; black holes; high energy astrophysics; x-ray astronomy